The Rise of Majorities and Emerging Existential Threats to India and China. (30th June 2020) - Castellino, Joshua
Abstract: China and India are comparable in size, complexity, and their relatively recent State-building histories. Commencing in 1947 and 1949 respectively, the relatively recent foundations of India and China highlighted a 'unity in diversity' message. The significance of this lay as much in ideology as in a pragmatism that was both central and relatively successful in bringing what could be argued as many civilizations into singular modern States. While the messages about diversity have always been contested in some quarters by rival ethno-nationalists, they remained significant in laying the foundations for a strong 'national' identity. To the majority populations, Hindu in India and Han in China this called for restraint to any triumphalism or chauvinism; to the minorities, they called for unshakeable loyalty in return for full citizenship rights. In both cases, these messages were backed by constructive affirmative action measures that, irrespective of their efficacy, served to emphasize the 'unity in diversity' message, sowing a degree of fealty towards the State over what may have been more prominent and compelling ethno-religious or ethno-linguistic cleavages. In recent years, however, this message has been significantly altered, as political majoritarianism has begun to oust legally or administratively determined minority protections. This article seeks to offer an assessment of the potential impact on this phenomenon on each country, arguing that it has contributed to instability, sowing seeds for the rise of opposing sub-national identities that the founding parents of each State actively sought to counter in their statecraft.